Effectiveness of self-instructional module on knowledge regarding dietary management of iron deficiency anemia among pregnant women attending outpatient department - Chauhan, Ramesh S.; John, Rashmi P.; Lata, Suman; Deo, Sujata (International Journal Of Community Medicine And Public Health, 2022)
Background: Anaemia is a big health issue in the world, and iron deficiency anaemia is one of the commonest types of anaemia amongst them. The incidence rate of anaemia during pregnancy has been reported high around 40-80%. This study aimed to observe the effectiveness of self-instructional module on knowledge regarding dietary management of iron deficiency anaemia among pregnant women attending outpatient department (OPD). Methods: The research approach was quantitative and one group pre-test – post-test control design sample size was 80 women selected by non-probability purposive sampling technique fulfilling the inclusion criteria. Results: The researcher compared the calculated t value i.e. 6.04 with the critical value (2.00) on 0.05 level of significance (df=79). Since the calculated value lied beyond the critical value the alternative hypothesis was accepted. So there was a significant change in the pre-test and post-test knowledge score of pregnant women regarding dietary management on iron deficiency anemia. Conclusions: The researcher concluded that the self-instructional module was helpful in improving the level of knowledge among pregnant women. Self-instructional module can be a part of antenatal clinics/OPD and we can apply this for the future studies for prevention of anemia and management of anemia among pregnant women.